Association of taurine intake with changes in physical fitness among community-dwelling middle-aged and older Japanese adults: an 8-year longitudinal study - Domoto, Takashi; Kise, Kazuyoshi; Oyama, Yukiko; Furuya, Kanae; Kato, Yuki; Nishita, Yukiko; Kozakai, Rumi; Otsuka, Rei (Frontiers in Nutrition, 2024)
Introduction: Taurine has diverse valuable biological functions, including antioxidant activity and regulation of osmotic pressure. Maintaining physical fitness from middle age is important for healthy life expectancy. Although taurine administration improves muscle endurance and strength, its role in maintenance remains unclear. We aimed to clarify the longitudinal taurine intake association with fitness changes. Methods: Participants comprised men and women aged ≥40 years who participated in the third (2002-2004; Baseline) and seventh (2010-2012; Follow-up) waves of the National Institute for Longevity Sciences-Longitudinal Study of Aging (NILS-LSA) and completed a 3-day dietary weights recording survey at baseline. A table of taurine content was prepared for 751 foods (including five food groups: Seaweed; Fish and shellfish; Meat; Eggs; and Milk and dairy products) from the Standard Tables of Food Composition in Japan (1,878 foods) 2010. Four physical fitness items (knee extension muscle strength, sit-and-reach, one-leg standing with eyes closed, and maximum walking speed) were measured at baseline and follow-up. We analyzed the association of taurine intake with physical fitness change, employing a general linear model (GLM) and trend tests for baseline taurine intake and follow-up fitness change. Adjustments included baseline variables: sex, age, height, weight, educational level, self-rated health, smoking status, depressive symptoms, and clinical history. Results: The estimated average daily taurine intake (standard deviation) was 207.5 (145.6) mg/day at the baseline. When examining the association with the four physical fitness parameters, higher taurine intake positively increased the change in knee extension muscle strength (T1; 0.1, T2; 0.8, T3; 1.1 (kgf) GLM, p<0.05; p for trend <0.05) and reduced the decline in knee extension muscle strength in the subgroup analysis of participants aged ≥65 years (T1: -1.9, T2: -1.7, T3: -0.4 kgf; GLM p<0.05, p for trend <0.05). No relationship was found between taurine intake and the remaining three fitness factors. Conclusion: Estimation of taurine intake showed that dietary taurine intake potentially contributes to the maintenance of knee extension muscle strength over 8 years among Japanese community-dwelling middle-aged and older individuals. This is the first study to investigate the association of dietary taurine intake with muscle strength.